Efficacy of selected control agents against the black bean aphid (Aphis fabae) in Najaf governorate, Iraq - Alyaa Muslim Noori; Khudheyer A.A. Alnomani (Journal of Kerbala for Agricultural Sciences, 2025)
This study was conducted to evaluate the efficacy of selected control agents against the black bean aphid (Aphis fabae), with the experimental design comprising two primary components. The first involved a laboratory assessment of three control agents: the insect growth regulator Match, the botanical insecticide Oxymatrine, and the Entomopathogenic fungus Metarhizium anisopliae, each tested at concentrations of 0%, 50%, and 100% with three replicates per treatment. Based on laboratory findings, the optimal concentration (100%) for each agent was selected for subsequent field application. In the field experiment, treatments included individual applications of each agent and a combined application (Match + Oxymatrine + M. anisopliae) as an integrated spray treatment. The experimental design also incorporated an evaluation of the effect of bean cultivar on aphid mortality. Laboratory results demonstrated a marked efficacy of the 100% concentration for all agents tested. Match induced mortality rates of 88.44% and 83.55% for nymphal and adult stages, respectively; Oxymatrine achieved 96.67% and 97.78%, while M. anisopliae resulted in 63.75% and 62.39% mortality among nymphs and adults, respectively. Field experiment outcomes revealed a significant increase in adult aphid mortality following application of the combined treatment (Match + Oxymatrine + M. anisopliae), which yielded the highest mortality rate 122.12 adults per plant. In contrast, the control treatment exhibited no mortality throughout the study.